2020
DOI: 10.1038/s41598-020-77951-w
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting aesthetic chills using a wearable prosthesis improves their downstream effects on reward and social cognition

Abstract: Previous studies on aesthetic chills (i.e., psychogenic shivers) demonstrate their positive effects on stress, pleasure, and social cognition. We tested whether we could artificially enhance this emotion and its downstream effects by intervening on its somatic markers using wearable technology. We built a device generating cold and vibrotactile sensations down the spine of subjects in temporal conjunction with a chill-eliciting audiovisual stimulus, enhancing the somatosensation of cold underlying aesthetic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 60 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…Recent studies have demonstrated that affective states can be elicited by triggering psychogenic shivering (PS) (Haar et al, 2020;Schoeller, et al, 2019a), using a device that controls the temperature in the upper back of the participants. Additional research indicates that the ability to be empathetic with others' emotions can be influenced by delivering electrical stimulation in the vagus nerve (Colzato et al, 2017), and by inducing affective states in the observer through videos (Pinilla et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that affective states can be elicited by triggering psychogenic shivering (PS) (Haar et al, 2020;Schoeller, et al, 2019a), using a device that controls the temperature in the upper back of the participants. Additional research indicates that the ability to be empathetic with others' emotions can be influenced by delivering electrical stimulation in the vagus nerve (Colzato et al, 2017), and by inducing affective states in the observer through videos (Pinilla et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preliminary evidence on a small sample recently indicated that augmenting sensory signals that mimics the physical experience of aesthetic chills can enhance individual social-affective cognition (e.g., empathy and pleasure; 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, how can one reinterpret such results in light of our present findings? Is it environmental exposure over one's own lifetime to art and poetry that is causally shaping the connectivity as seen in Williams et al 34 or is it more a priori predisposition that makes individuals better at integrating sensory information with their internal states, or alternatively more sensitive to sensory signals such as the ones seen in Haar et al 56 , that makes them more likely to reach such peaks of emotional-hedonic experiences? Clearly, further studies are needed to answer these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies attest to the complex, dynamic, and continuous interaction between cognitive and affective empathy, such as during passive observation of emotions or pain (Christov-Moore and Iacoboni, 2016), passive observation of films depicting personal loss (Raz et al, 2014), reciprocal imitation (Sperduti et al, 2014), tests of empathic accuracy (Zaki et al, 2009), and comprehension of others' emotions (Spunt and Lieberman, 2012), at the level of transcranial magnetic stimulation (TMS)--induced motor evoked potentials (MEPs), a functional readout of motor excitability (Gordon et al, 2018), and even in their neural substrates at rest (Christov-Moore et al, 2020). Indeed, recent studies using emotion prosthetics or interoceptive technologies have shown the importance of bodily signals in that process of identification (Schoeller et al, 2020;Haar et al, 2021). By stimulating the somatic markers of the emotion, Schoeller, Haar and Jain were able to enhance the prosocial effects of aesthetic chills (psychogenic shivers felt down the spine) during a film Haar et al, 2020).…”
Section: Alignment Feeling and Empathy In Aimentioning
confidence: 99%